PERLINDUNGAN HUKUM BAGI INVESTOR TERHADAP KEJAHATAN INSIDER TRADING DALAM PASAR MODAL INDONESIA - Hariono, Wisnu Satrio (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
Insider Trading or insider trading is a form of banned trading in securities transactions in the capital market. The practice of insider trading is one form of violation of the principle of openness which is the soul of the capital market industry. This research is motivated by the number of insider trading practices in securities transactions. The main problem to be answered through this research is to know the extent of Capital Market Law in handling insider trading practices in Indonesia capital market. This research uses normative juridical approach and comparison of laws. In this research can be found the existence of legal efforts that can be done by investors who are harmed by the crime of insider trading by filing a lawsuit Unlawful Act, as a form of legal protection for investors.